The Influence of Media Conglomerates in the Context of Migration from Analog to Digital Broadcasting: Analysis from a Media Political Economy Perspective and Its Impact on Society - Prabowo, Agung; Cahyandari, Rini; Abdul Halim, Nurfadhlina (Communication In Research And Publications, 2024)
This research discusses the role of media conglomerates in the context of migration policies from analog to digital broadcasts. Media conglomerates often have great influence in the media industry, and migration policies such as these can affect the way information is delivered and accessed by the public. This research analyzes the tendency of media conglomerates to report information that suits their interests, their impact on society, and how they respond to digital migration policies. The political economy of communication theory, especially the concepts of commodification, spatialization, and structuration, is used to explain these dynamics. Some media conglomerates reject the migration policy, considering it a threat to their dominance in the media industry. However, migration policies also open up opportunities for new entrants in the broadcasting industry. In conclusion, it is important to understand how the dynamics of the political economy of the media influence media policies that affect society.